1998
DOI: 10.1002/(sici)1096-9861(19980817)398:1<25::aid-cne3>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Entorhinal cortex of the rat: Topographic organization of the cells of origin of the perforant path projection to the dentate gyrus

Abstract: By using three-dimensional computer reconstruction techniques and the production of two-dimensional unfolded maps, we analyzed the topographic organization of projections from the entorhinal cortex of the rat to the dentate gyrus. The retrograde tracers, Fast blue and Diamidino yellow, were injected at all septotemporal levels of the dentate gyrus, and the distribution of retrogradely labeled layer II cells in the entorhinal cortex was plotted by using computer-aided microscopy systems. Discrete injections of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
145
0
5

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(164 citation statements)
references
References 15 publications
14
145
0
5
Order By: Relevance
“…Labeled fibers arising from EC injection sites waser also analyzed with respect to the band of origin. The location of the bands were estimated based on the analyses and descriptions reported in the earlier study by Dolorfo and Amaral (1998b; 1998a). Labeled fibers were quantified for subregions within the piriform, frontal, insular, temporal, cingulate, parietal, and occipital cortices (see Nomenclature section and Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Labeled fibers arising from EC injection sites waser also analyzed with respect to the band of origin. The location of the bands were estimated based on the analyses and descriptions reported in the earlier study by Dolorfo and Amaral (1998b; 1998a). Labeled fibers were quantified for subregions within the piriform, frontal, insular, temporal, cingulate, parietal, and occipital cortices (see Nomenclature section and Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…The EC in rats and monkeys is organized into multiple bands that project to different septotemporal levels of the dentate gyrus (Witter, 1989; Witter et al, 1989b; Dolorfo and Amaral, 1998b; Dolorfo and Amaral, 1998a). Dolorfo and Amaral (1998b; 1998a) showed that the EC is organized into three bands that project to different septotemporal levels of the dentate gyrus (DG, Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The perirhinal and parahippocampal cortices have strong and largely reciprocal interconnections with the frontal, temporal, and parietal lobes as well as the cingulate, retrosplenial, and insular cortices (Van Hoesen et al, 1972;Martin-Elkins and Horel, 1992;Suzuki and Amaral, 1994a;Lavenex et al, 2001). The perirhinal and parahippocampal cortices also have strong and reciprocal projections with the entorhinal cortex Suzuki and Amaral, 1994b), the major cortical input of the hip-pocampus (Dolorfo and Amaral, 1998). Convergent findings from human neuropsychological studies (Scoville and Milner, 1957;Stefanacci et al, 2000) together with findings from lesion (Mishkin, 1978;Zola-Morgan and Squire, 1985) and neurophysiological (Miller et al, 1993;Suzuki et al, 1997) studies have shown that that entorhinal, perirhinal, and parahippocampal cortices, together with the hippocampus, are essential for normal declarative memory.…”
mentioning
confidence: 99%